Hunting for molecules in schizophrenia through omics technologies - Ceren Acar (Medicine Science, 2020)
Schizophrenia is a complex mental disorder that affects 1% of the population worldwide with ~80% heritability rate. This mental disorder has dramatic impacts not only on the patients but also on the society as well. Unfortunately our knowledge about the molecular mechanisms underlying the disease is limited. To understand the pathological mechanisms that lead to disease phenotype we need to use genomics, transcriptomics, epigenomics, proteomics, metabolomics like approaches with newly developed technologies. These approaches will also help scientist to find out new diagnostic tools that can be used as biomarkers in a complex disease like schizophrenia or personalized therapy strategies. It is possible to map the molecular changings in disease and healthy state with the help of the OMICS based technologies. This review sheds light on these OMICS based approaches to hunt the biomarkers that can be used as diagnostic tools for schizophrenia and other mental disorders or to figure out the candidate molecules for new treatment options. [Med-Science 2020; 9(1.000): 270-3]